Isolation and Identification of Secondary Metabolite Compounds of Laor Worm Extract as Antibacterial - Martha Kaihena; Mas’uth Pratomo MS; Abdul M Ukratalo (Ridwan Institute, 2022)
Laor worms (Lysidice oela) are worms that appear on the surface of the Maluku sea to reproduce in March or April. Laor worms are usually consumed by most people because they contain 13.92% protein, 81.51% water, 1.01% fat, and 2.41% ash and contain 9 types of essential amino acids. Secondary metabolite compounds (bromophenol) from marine worms are antimicrobial. This research aimed to determine the potential of secondary metabolites in inhibiting the growth of E. coli bacteria and to determine the secondary metabolites contained in laor worms. Laor worm is extracted maceration with ethanol, ethyl acetate and petroleum ether. The results of each extract were tested for antibacterial activity using the disc diffusion method with variations in concentrations of 25, 50, 75, 100, and 125 mg/mL against E. coli bacteria. The results of the extract which had the highest antibacterial activity were then tested for phytochemicals, then separated using TLC, and identified active compounds using UV-Vis spectrophotometers and their functional groups using FT-IR spectrophotometers. The results showed that laor worm extract could inhibit the growth of E. coli bacteria with an inhibition zone area of ??13.4 mm for ethanol extract; 14.8 for ethyl acetate extract and 12.6 mm for petroleum ether extract. The phytochemical test showed that the ethyl acetate extract of la worms contained flavonoids, saponins, steroids, triterpenoids, and alkaloids. Identification using a UV-Vis spectrophotometer obtained ?max was 203 nm which showed steroid compounds. The identification of active compounds using an FTIR spectrophotometer shows the functional groups O-H, C = O, C-C, C-OH primary, and C-H which are thought to be steroid compounds.